STIMULUS DAN RESPONS DALAM TEORI BELAJAR BEHAVIORISME (TINJAUAN VAIŚEṢIKA DARŚANA) : (Tinjauan Vaiśeṣika Darśana) - Nanda Jaya Pratama, I Gede; Maharani, Ni Putu Febbyana; Putri, Ni Kadek Ratna Chiaki; Wijayanti, Ni Kadek Hery; Atmajayanti, Ni Made Purnamiasih; Mawarni, Sherly Tegar; Sutriyanti, Ni Komang (Sphatika: Jurnal Teologi, 2025)
The development of science is supported by the emergence of various theories of knowledge put forward by experts. These theories and knowledge are based on philosophy, as the forerunner of all science. One of them is the theory of behaviorism, which was born from the point of view of the philosophy of education put forward by various western philosophers. Meanwhile, if viewed from a historical line, the development of eastern philosophy has existed earlier than western philosophy. As an eastern-based education, education in Indonesia can be explored and in accordance with western research, especially regarding learning theory. In this study, the researcher reviews how the elements of behaviorism theory in the perspective of Vaiśeṣika Darśana, as a school of eastern philosophy. This research is a qualitative type of research and is studied through a qualitative descriptive method. It uses a literature study approach in collecting relevant information. The results of this study show the linkage of elements of behaviorism theory especially operant conditioning theory proposed by B.F. Skinner involving stimulus and response in learning with padārtha in Vaiśeṣika Darśana. The existence of stimulus and response aspects is found as padārtha specifically in the object of karma described in Vaiśeṣika Śūtra. In its realization, stimulus and karma are identified in the actions taken by the teacher in the learning process, in the form of providing material, assignments, learning models and class rules. In the learning process, the teacher acts as a stimulus presenter so that students can respond in accordance with the teacher's expectations.